Matematyczna aktywność badawcza uczniów klas początkowych. Między koncepcjami naukowymi i potocznymi - Alina Kalinowska (Problemy Wczesnej Edukacji)
Conditions stimulating an independent creation and formulation of regularities require particular cognitive scenarios. In the early grades, students have the opportunity to develop this all-compassing intellectual ability mostly due to the specially designed educational and explorative conditions. The paper is an attempt to present a common understanding of mathematical analysis done by the students in the early grades and offers an alternative way of perceiving sush inquiries during the class.